2021
DOI: 10.5334/aogh.3135
|View full text |Cite
|
Sign up to set email alerts
|

A Critique of Helsinki Criteria for Using Lung Fiber Levels to Determine Causation in Mesothelioma Cases

Abstract: Asbestos is a known human carcinogen and the chief known cause of mesothelioma. In 1997, a group of experts developed the Helsinki Criteria, which established criteria for attribution of mesothelioma to asbestos. The criteria include two methods for causation attribution: 1) a history of significant occupational, domestic, or environmental exposure and/or 2) pathologic evidence of exposure to asbestos. In 2014, the Helsinki Criteria were updated, and these attribution criteria were not changed. However, since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Cosmetic talc is a component of body powders, facial and eye makeups, and some animal flea powders [23]. Although asbestos is a trace impurity of cosmetic talc, concentrations of amphibole asbestos during the application of cosmetic talc powders have been measured at ~2.7-4.5 f/cc, which is orders of magnitude greater than current urban background levels (0.0001 f/cc) [13,16].…”
Section: Cosmetic Talc Usementioning
confidence: 96%
See 1 more Smart Citation
“…Cosmetic talc is a component of body powders, facial and eye makeups, and some animal flea powders [23]. Although asbestos is a trace impurity of cosmetic talc, concentrations of amphibole asbestos during the application of cosmetic talc powders have been measured at ~2.7-4.5 f/cc, which is orders of magnitude greater than current urban background levels (0.0001 f/cc) [13,16].…”
Section: Cosmetic Talc Usementioning
confidence: 96%
“…Actinolite is not found in any commercial product other than talc. Tran et all have suggested that finding talc together with tremolite/actinolite/anthophyllite in fiber burden analyses of tissues is prima facie evidence of cosmetic talc use [11].…”
Section: Talcmentioning
confidence: 99%